The role of social support, coping strategy, and severity of exposure on children's resiliency - Egargo, Faye Jessa D.; Pestilos. Cristy C.; Sison, Jaycel M. (2015)
As the occurrence of disaster increases globally, children are among those high at risk with the negative consequences of disaster. Children may be vulnerable but they also have unique capacities to adapt in times of disasters typically termed as resiliency. Hence, the present study is centered on understanding children's resilience through the evaluation of predictive capacities of factors such as severity of exposure, social support, coping strategy through engagement, and coping strategy through disengagement. Data were gathered from 382 participants with age ranging from 9 to 12 years old and who are belonging from grades 4, 5, and 6. Using Standard Multiple Regression Analysis, results showed that children's resiliency can be predicted by the combination of the predictor variables used in this study F(4,377)= 77.77, p < 0.05. Among the predictor variables, social support and coping strategy through engagement have significantly contributed to children's resilience. This finding is discussed using Bronfenbrenner's Bioecological model. Practical implications of the present study that will enhance structures of external social support as well as active coping strategies among children in the context of disasters are also discussed.